Dynamic Governanc e Pekanbaru City in Policy Implementation About The New Normal in Pandemic Covid-19 Era - Resa Vio Vani; Dedi Kusuma Habibie; Maryani Maryani (Iapa Proceedings Conference, 2020)
Dynamic Governance shown in this study aims to reveal various programs and activities within the scope of government that must always be oriented towards the public interest with the various challenges and anticipatory requests for Covid19 on the implementation of a new lifestyle policy in Pekanbaru City with policies, understanding the objectives that must be implemented. overall. This study aims to see the Dynamic Government of Pekanbaru City in Implementing the New Lifestyle Policy during the Covid19 pandemic. The method used in this research is a qualitative method based on the postpositivism or interpretive philosophy, used to examine the conditions of natural objects, where the researcher is the key instrument. This result is that government programs in overcoming Covid19 through the New Lifestyle policy, research have not answered existing problems so that they have not been able to produce and implement adaptive policies (adaptive policies) through the development of dynamic capabilities (including the ability to think ahead, think again, and think crosswise. ) in the process of implementing the New Lifestyle policy during the Covid pandemic19